Petrichor - Rees, Melanie (Bassendean, W.A. : Hague Publishing, 2021)
Drought has turned the paddocks of Paddle Creek Station to dust. Now the death of Clayton's older brother has shaken his family to its core and left a gaping hole in Clayton's memory. A hole his parents won't even discuss. When Waringa, in the shape of a fox-spirit, tells Clayton it's up to him to save his family and to free the rain spirits held prisoner by the demonic Red King, Clayton must find a strength within himself he never knew he possessed. But as Waringa guides Clayton towards his ultimate battle with the Red King, his quest brings his whole family closer to the abandoned homestead where his brother died. And as it does Clayton's actions uncover raw wounds, forcing hidden memories to surface.
Keywords: 2000-2099; Australian fiction -- 21st century; Evil -- Fiction; Australian fiction; Fantasy; Good and evil; Electronic books; Fiction